HUBUNGAN AKTIVITAS SEKSUAL USIA DINI DENGAN HASIL PEMERIKSAAN PAP SMEAR SEBAGAI DETEKSI DINI KANKER SERVIKS DI KABUPATEN SIDOARJO - Acivrida Mega Charisma, Farida Anwari (AKADEMI FARMASI JEMBER, 2017)
Cervical cancer is the number one cause of death in Indonesian women. Cervical cancer is a malignant tumor that grows inside the cervix / cervix is the lowest part of the uterus attached to the top of the vagina.Terjantung cancer always begins with precancerous conditions which further leads to advanced cancer conditions. Pap smear test is a test that is accurate enough to detect early cervical cancer if routinely performed, because this test can detect any abnormal cells changes. This study aims to determine the relationship between sexual activity performed at an early age by the respondents with the results of pap smear examination.This research use cross sectional analysis method, simple random sampling sample of 184 people. The result is made of frequency table, cross tabulation and then analyzed by chi square test and spearman correlation test.The results showed that the results of Pap smears class II and III (Not In Normal Limit) on the respondents who do sexual activity at age 18 years there are 45 (71.4%) people and the respondents who do not do sexual activity at age 18 years only 41 (33.9%) people. The same thing happened for the age factor, in respondents with age 35 (at risk) there were 66 (54,2%) people who had the result of examination of Class II and III papsmear (Not in Normal Limit) and at age 35 years old only 20 (33.3%) persons who have the results of papsmear examinations Class II and II (Not In Normal Limit). The analysis using chi square test showed significant correlation between age and early age sexual activity with pap smear with indigo ρ = 0.025 and ρ = 0.018 (α = 0.05).The hope of this study can be an important lesson for the younger generation to be able to control the association in order to avoid doing activities at the age of too young and for all married women (ever doing sexual activity) to perform pap smear examination early to detect any abnormalities before developed into cancer.Keywords : early childhood sexual activity, cervical cancer, pap smear, cervical cancer risk factor